An empirical analysis of the determinants of financial reporting quality in Japanese nonprofit organizations: focusing on governance - Enomoto, Yoshihito; Basiruddin, Rohaida; Nakashima, Masumi (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2025)
Nonprofit organizations play an important role in Japan. Yet, very few empirical studies, to our knowledge, have examined the financial reporting quality and governance of Japanese nonprofit organizations empirically. Addressing this research gap, we developed and tested hypotheses on financial reporting quality and governance. First, in terms of their characteristics, Japanese nonprofit organizations can be categorized by the type of competent authority system under which they function. In Japan’s nonprofit sector, competent authorities provide guidance and supervision to correct reckless management. External audits are only mandated for certain nonprofit organizations. Second, governance might suppress earnings management within accounting standards in these organizations. Furthermore, earnings management may be reduced by decreasing pressure and incentives within and outside the organization. It is suggested that governing bodies and accounting standards should be unified. Legal supervision by governing bodies and audits might be ineffective. Finally, we propose future directions for the governance of Japanese nonprofit organizations.